A Nonheme Thiolate-Ligated Cobalt Superoxo Complex: Synthesis and Spectroscopic Characterization, Computational Studies, and Hydrogen Atom Abstraction Reactivity - Gordon, Jesse B; Vilbert, Avery C; Siegler, Maxime A; Lancaster, Kyle M; Moënne-Loccoz, Pierre; Goldberg, David P (Journal of the American Chemical Society, 2019)
The synthesis and characterization of a Co(II) dithiolato complex Co(Me TACN)(S SiMe ) (1) are reported. Reaction of 1 with O generates a rare thiolate-ligated cobalt-superoxo species Co(O )(Me TACN)(S SiMe ) (2) that was characterized spectroscopically and structurally by resonance Raman, EPR, and X-ray absorption spectroscopies as well as density functional theory. Metal-superoxo species are proposed to S-oxygenate metal-bound thiolate donors in nonheme thiol dioxygenases, but 2 does not lead to S-oxygenation of the intramolecular thiolate donors and does not react with exogenous sulfur donors. However, complex 2 is capable of oxidizing the O-H bonds of 2,2,6,6-tetramethylpiperidin-1-ol derivatives via H atom abstraction. Complementary proton-coupled electron-transfer reactivity is seen for 2 with separated proton/reductant pairs. The reactivity studies indicate that 2 can abstract H atoms from weak X-H bonds with bond dissociation free energy (BDFE) ≤ 70 kcal mol . DFT calculations predict that the putative Co(OOH) product has an O-H BDFE = 67 kcal mol , which matches the observed pattern of reactivity seen for 2. These data provide new information regarding the selectivity of S-oxygenation versus H atom abstraction in thiolate-ligated nonheme metalloenzymes that react with O .